The role of civil society in advancing global citizenship - Scott Carlin; YuKang Choi (UN Chronicle, 2018)
It is the responsibility of civil society to experiment with models of effective global citizenship, to understand, care and act on behalf of people and the planet through ecological and socially inclusive principles and practices. Global citizenship is transforming the worlds of art, business, culture, education, human and labour rights, religion, public health, politics and our relationship with nature.